"A SURVEY ON ATTITUDES AND KNOWLEDGE OF JALIL-ABAD RURAL COMMUNITY IN RELATION TO DRINKG WATER" - F. Shafii; K. Imandel; H. Dast-Kotah (Tehran University of Medical Sciences, 1978)
For purposes of planning and programming of environmental health activities at the community level, it is important to gather information regarding people's need, demands, and the basic socio demographic data, as well as relevant community resources. It is more likely, that in this way, the people not only will participate and get involved with the programme, but the health activities will be more appropriate to their needs. This descriptive exploratory survey, aimed at gathering sociodemographic data, and information about community's attitudes and knowledge about their drinking water, and its degree of safety, as far as the health of people is concerned. The rural community under the study is Jalil-Abad village with 325 inhabitants, located near Garmsar, south-east of Tehran. The study carried out on 70 households, selected by random sampling technique. The data has been collected by various means: available documents, questionnaires, observation, and laboratory tests for the analysis of drinking water. The findings revealed that the population structure of this rural community is young, with an average size of he family of 4.6. Eighty per cent of the population is illiterate and 11.4 per cent had education to the primary level; over one quarter of the families (25.7 per cent) had an annual income of less than 50.000 rials nearly 13 per cent had more than 200.000 rials and the remaining between these figures. The environmental health facilities are poor and the drinking water is collected manually by public system through several brooks branching out from Hableh-Roud River, the population draws their drinking water from the public taken. The laboratory tests on ten water samples from existing drinking water showed that water has been contaminated by bacteria. (Minimum M.P.N. and Fecal M.P.N. were 1100 and 1000 per 100 ml respectively.) Considering the maximum allowable concentration of 45 mg/l as Nō3 for Nitrate in drinking water in United States and W.H.O. standard, the minimum concentration of Nitrates in Jalil-Abad drinking water (55mg/I as Nō3) This implies that necessary measures should be taken before water is to be consumed for domestic purposes, though the most common diseases among the infants under 5 years of age is reported to be diarrhea, which can be assumed that its main reason should be chemical (Nitrate) and bacterial contamination of water. In general the population under the study has relative knowledge about the relationship between sickness and unhealthy environment, particularly drinking water. Although most of the people under the study stated that the existing water should be boiled in order to make it safe for drinking, but failed to do so regularly. It can be concluded that the people of the community stressed their desire for cooperation in the improvement of the existing drinking water.